Highly Efficient Single‐Unit White OLED Device with Emission from Both Singlet and Triplet Excitons. Issue 1 (June 2014) - Ishisone, Takahiro; Seo, Satoshi; Nonaka, Yusuke; Kawata, Takuya; Ohsawa, Nobuharu
Abstract We succeeded in developing a single‐unit hybrid organic light‐emitting diode (OLED) device with efficient light emission from both a phosphorescent layer and a fluorescent layer. The single‐unit hybrid OLED achieved power efficiency higher than that of a two‐unit hybrid tandem OLED with a phosphorescent and fluorescent layers.